Identifying evidence and knowledge gaps for designing development interventions: Process lessons from Titukulane in Malawi - Babu, Suresh Chandra; Patterson, Andrew; Malunga, Anthony; Ranaivoarivelo, Nivo (CARE Malawi, 2020)
Programs must tailor their interventions to fit the needs and contexts of program participants to achieve maximum success, even if those interventions are based on previously successful approaches and models. Tailoring interventions requires a comprehensive understanding of socio-economic, cultural and geographic circumstances for program participants, including vulnerable women, men, youth, and the elderly. Usually much of this information, also known as evidence and knowledge gaps (EKGs), is missing, and the program conducts multiple studies and assessments to fill these EKGs.